The Broad Autism Phenotype Questionnaire: Prevalence and Diagnostic Classification. Issue 2 (20th February 2013) - Sasson, Noah J.; Lam, Kristen S. L.; Childress, Debra; Parlier, Morgan; Daniels, Julie L.; Piven, Joseph
<x xml:space="preserve">Abstract</x> The Broad Autism Phenotype Questionnaire (BAPQ) was administered to a large community‐based sample of biological parents of children with autism (PCAs) and comparison parents (CPs) (n = 1, 692). Exploratory factor analysis and internal consistency parameters confirmed a robust three‐factor structure of the BAPQ, corresponding to the proposed aloof, pragmatic language and rigidity subscales. Based upon the distribution of Broad Autism Phenotype (BAP) features in the general population, new normative cutoff values for BAPQ subscales were established that provide increased specificity relative to those previously reported, and thus enhance the utility of the BAPQ for diagnostically classifying the BAP. These cutoffs were also used to estimate prevalence of the BAP and its three components, with rates ranging between 14–23% for PCAs and between 5–9% for CPs. Analysis of patterns of BAP characteristics within family members revealed that BAP features were more likely to co‐occur in PCAs relative to CPs. Collectively, these findings extend the utility of the BAPQ and provide additional evidence that it is an efficient and reliable tool for disaggregating the heterogeneity of autism through the identification of meaningful subgroups of parents. Autism Res 2013, 6: 134–143. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.